2021
DOI: 10.1007/s11332-021-00780-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sleep between youth elite amateur athletes and professional athletes

Abstract: Recent studies suggest that professional athletes seem to experience significant sleeping problems. However, little is still known about the occurrence of sleeping challenges at different stages of an athletic career. This descriptive study aimed to compare the sleep of professional athletes with younger elite amateur athletes. A total of 401 sportsmen, 173 youth elite amateur athletes and 228 professional athletes fulfilled a validated questionnaire. The self-estimated quality of sleep (on a linear scale 0–10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
(70 reference statements)
0
3
1
Order By: Relevance
“…However, the small sample size of the current study ( n = 15) must be noted. This is in stark contrast to a recent investigation in Finland ( n = 228) which demonstrated that 33.9% ( n = 76) used sleep medication [ 38 ]. A report from the National Collegiate Athletic Association (NCAA) indicated that sleep medication use accounted for 10.3% of miscellaneous substance use across all sports in American student athletes [ 39 ].…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…However, the small sample size of the current study ( n = 15) must be noted. This is in stark contrast to a recent investigation in Finland ( n = 228) which demonstrated that 33.9% ( n = 76) used sleep medication [ 38 ]. A report from the National Collegiate Athletic Association (NCAA) indicated that sleep medication use accounted for 10.3% of miscellaneous substance use across all sports in American student athletes [ 39 ].…”
Section: Discussioncontrasting
confidence: 90%
“…Previous research using both subjective [ 33 ] and objective measures [ 34 ] has suggested that elite athletes have inferior sleep quality compared to non-athletes. Poor sleep quality is of particular concern for elite athletes as it can result in a reduction in recovery and/or subsequent athletic performance [ 4 , 35 , 36 , 37 , 38 ]. While there were improvements from baseline to post-intervention in PSQI dimensions of sleep onset latency (1.67 ± 0.49 to 1.35 ± 0.62), sleep duration (0.34 ± 0.49 to 0.14 ± 0.35) and sleep efficiency (0.6 ± 0.91 to 0.2 ± 0.42), no significant differences were observed.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in accordance to that reported by Madigan et al [ 31 ] in a study between elite and sub elite athletes without difference of poor sleep between both groups. However, in a recent study of Penttilä et al [ 32 ] it was noticed an important proportion of poor sleep in professional athletes compare to amateur. With regards to physiological and psychological complexity of sleep, the poor quality of sleep should be superior in professional athletes due to the important mental stress and physical demands.…”
Section: Discussionmentioning
confidence: 96%
“…[18] While this study was not specifically conducted on junior athletes, the mean ages of the participants (20 years old) is close to the mean age of 17 in our study. However, there may be differences in sleep parameters between junior and adult elite athletes, [19] highlighting the need for more research on this young population. Sleep behavior may be affected by a multitude of factors, of which the causality was not feasible to assess in this study.…”
Section: Discussionmentioning
confidence: 99%